Climate Variability and Household Welfare Outcomes in Uganda - Babyenda, Peter; Kabubo-Mariara, Jane; Odhiambo, Sule (University of Dar es Salaam, 2021)
This study examines the impact of climate variability on household welfare outcomes in Uganda by combining long-term climate data (1979-2013) interpolated at household level, and six waves of the Uganda National Panel Survey (2009-2019). Pooled average ordinary least squares and random effects models are used for empirical analysis. The results indicate that climate variability has a significant nonlinear impact on household welfare outcomes. Access to extension services, value of household assets, education level, gender and location of the household head were also found to influence Uganda’s household welfare outcomes. These findings, therefore, highlight the need for policymakers to move swiftly to counter climate variability and its effects by designing and adopting appropriate measures that mitigate climate variability, and enhance household welfare outcomes among the people of Uganda.